Anesthetic implications in hyperthermic intraperitoneal chemotherapy - Nishkarsh Gupta; Vinod Kumar; Rakesh Garg; Sachidanand Jee Bharti; Seema Mishra; Sushma Bhatnagar (Wolters Kluwer Medknow Publications, 2019)
Patients with peritoneal carcinomatosis were considered incurable with dismal survival rates till hyperthermic intraperitoneal chemotherapy after optimal cytoreductive surgery evolved. Perioperative management for these procedures is complex and involves an optimal cytoreductive surgery followed by hyperthermic intraperitoneal chemotherapy. In this article we highlight the perioperative concerns in these patients including anesthetic challenges, such as optimal fluid management, maintaining blood pressure, control of body temperature, coagulation and electrolyte derangement and renal toxicity of chemotherapeutic drugs. We have also discussed the postoperative problems and their management.